Pendampingan Pegiat Olahraga Tradisional Egrang Dalam Meningkatkan Kebugaran Jasmani di Kelurahan Jambangan Kota Surabaya - Yudi Dwi Saputra; Andun Sudijandoko; Made Pramono; Awang Firmansyah; Panji Bana (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
This mentoring activity aims to improve the physical fitness of the community through traditional stilt sports in Jambangan Village, Surabaya City. Stilts, as part of Indonesia's cultural heritage, have the potential to train balance, muscle strength, endurance, as well as the focus and concentration of its players. This program includes providing materials on physical fitness, correct stilt playing reflexology techniques, and direct practice sessions for participants. The results of the activity show that community participation in stilt games can improve their physical fitness while strengthening a sense of togetherness and awareness of the importance of preserving traditional culture. In addition, stilts are also a means of education for the younger generation to learn about traditional games that are beneficial for health. This program is expected to be able to create an active community that continues to develop traditional sports as part of a healthy lifestyle and local culture